2019
DOI: 10.1002/alr.22383
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal endoscopic resection of orbital cavernous hemangiomas: our experience with 23 cases

Abstract: Background:The aim of this work was to present our singlecenter experience on orbital cavernous hemangiomas managed using an endonasal endoscopic approach. Methods:The study design used was one-institutional retrospective review. Twenty-three cases of orbital cavernous hemangioma were analyzed and followed up.Results: There were 10 males and 13 females, with an average age of 46.1 years, included in our study. Seven cases were extraconal, 16 cases were intraconal, and in 10 of the patients the optic nerve was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…4,5 This framework, the Cavernous Hemangioma Exclusively Endonasal Resection (CHEER) system, categorizes tumors based on location and anticipated surgical complexity, and has been adopted by orbital surgeons worldwide. 6,7 Similar to OCHs, other benign orbital tumors (BOTs; eg, solitary fibrous tumors, schwannomas, and meningiomas) are also encapsulated and may be amenable to EER with similar outcomes. 6,8 These similarities suggest that an anatomic-based staging system, such as CHEER, may be applied to range of benign orbital tumor pathologies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 This framework, the Cavernous Hemangioma Exclusively Endonasal Resection (CHEER) system, categorizes tumors based on location and anticipated surgical complexity, and has been adopted by orbital surgeons worldwide. 6,7 Similar to OCHs, other benign orbital tumors (BOTs; eg, solitary fibrous tumors, schwannomas, and meningiomas) are also encapsulated and may be amenable to EER with similar outcomes. 6,8 These similarities suggest that an anatomic-based staging system, such as CHEER, may be applied to range of benign orbital tumor pathologies.…”
mentioning
confidence: 99%
“…In order to meet these needs, a staging system was introduced in 2019 for EER of orbital cavernous hemangiomas (OCHs), the most common adult benign orbital tumor (BOT) 4,5 . This framework, the Cavernous Hemangioma Exclusively Endonasal Resection (CHEER) system, categorizes tumors based on location and anticipated surgical complexity, and has been adopted by orbital surgeons worldwide 6,7 . Similar to OCHs, other benign orbital tumors (BOTs; eg, solitary fibrous tumors, schwannomas, and meningiomas) are also encapsulated and may be amenable to EER with similar outcomes 6,8 .…”
mentioning
confidence: 99%
“…12 Potential to damage the optic nerve will thereby be increased due to the visual obstruction by the tumor. 19 Access to Zone 2 via a prelacrimal approach employed the same corridor as the transethmoidal approach, the space between the medial and inferior recti muscles (average, 7.02 AE 0.33 mm). The inferior orbit between the infraorbital canal with the inferomedial ridge (average, 10.39 AE 0.35 mm) was removed to facilitate a prelacrimal entry into the inferomedial intraconal space.…”
Section: Discussionmentioning
confidence: 99%
“…cavernous hemangioma) via the corridor between the medial and inferior recti muscles has been reported, accessing the region between the medial rectus muscle and optic nerve ( Zone 2 ) remains challenging through a transethmoidal approach. 7,19 The superior border of the medial rectus muscle is approximately at the same level as the optic nerve, 20 and the average height of the medial rectus muscle is 11.07 ± 0.59 mm, which may constitute the obstacle for exposing the optic nerve via a transethmoidal approach. 21 Based on this cadaveric study, we found that the anteroinferior aspect of Zone 2 could be sufficiently exposed via a transethmoidal approach without retraction of the medial rectus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the surgical technique and experience introduced at a single institute are particularly worthy of reference. In a case series of patients with orbital cavernous hemangiomas medial to the optic nerve, Ma et al . summarized their experience with endoscopic transnasal resection of these hemangiomas at their institute, and concluded that this is likely a reasonable option for resection of the orbital tumor, which with greater experience, skilled surgical technique, and careful operation, can achieve better clinical efficacy.…”
mentioning
confidence: 99%